Letters, fictions, lives : Henry James and William Dean Howells - James, Henry, 1843-1916 (OUP E-Books., 1997)
This volume attempts to determine the early influence shared between William Dean Howells and Henry James by reconstructing and evaluating documentary evidence of their literary cross-fertilization. The 151 letters included represent each writer's most significant criticism of the other.